2019
DOI: 10.5125/jkaoms.2019.45.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Osteonecrosis of the jaw in the era of targeted therapy and immunotherapy in oncology

Abstract: Osteonecrosis of the jaw (ONJ) is a well-known pathological condition in oncology derived from the use of bisphosphonates (BPs) and denosumab. Many molecular and immunological targets have been introduced for daily use in cancer treatment in recent years; consequently, new cases of ONJ have been reported in association with these drugs, especially if administered with BPs and denosumab. When the drugs are administered alone, ONJ is rarely seen. The objective of our study was to analyze the recent literature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Of note, crizotinib inhibits MET proto-oncogene (MET) and Macrophage Stimulating Factor 1 Receptor (MST1R, also peviously known as RON), two receptors that regulate osteogenesis through Platelet Derived Growth Factor (PDGF). PDGF pathway is thought to be involved in sorafenib-and imatinib-induced osteonecrosis by reducing the activity of osteoclastogenic cytokines including macrophage colonystimulating factor (M-CSF) and receptor activator of nuclear factor kappa-Β ligand (RANKL) [17]. PDGF signalling might have been involved in our patient's osteitis.…”
Section: Discussionmentioning
confidence: 86%
“…Of note, crizotinib inhibits MET proto-oncogene (MET) and Macrophage Stimulating Factor 1 Receptor (MST1R, also peviously known as RON), two receptors that regulate osteogenesis through Platelet Derived Growth Factor (PDGF). PDGF pathway is thought to be involved in sorafenib-and imatinib-induced osteonecrosis by reducing the activity of osteoclastogenic cytokines including macrophage colonystimulating factor (M-CSF) and receptor activator of nuclear factor kappa-Β ligand (RANKL) [17]. PDGF signalling might have been involved in our patient's osteitis.…”
Section: Discussionmentioning
confidence: 86%
“…Antiresorptive use has increased in recent years due to new molecular targets and immunological drugs used for oncologic treatment. There has been a corresponding significant increase in MRONJ [ 10 ], which decreases the quality of life in these patients [ 8 ]. The antiresorptive drugs are classified into 5 classes, according to the principal agent: bisphosphonates, estrogen, selective estrogen receptor modulators, calcitonin, and denosumab.…”
Section: Discussionmentioning
confidence: 99%
“…Nifosi et al reported an increase in ONJ following oncologic treatment. Further, bone diseases such as osteoporosis are more common in postmenopausal women, due to hormonal alterations [ 10 ]. Zoledronic acid is a member of the third generation of bisphosphonates.…”
Section: Discussionmentioning
confidence: 99%
“…Among the potential mechanisms capable of inducing BONJ, an essential role is attributed to the possibility that bisphosphonates may have an antiangiogenetic action capable of delaying wound healing and/or affecting microinfarction in bone and/or soft tissues [52].…”
Section: The Downregulation Of Malat1 (Metastasis-associatedmentioning
confidence: 99%